2019
DOI: 10.3390/catal9030222
|View full text |Cite
|
Sign up to set email alerts
|

Immobilised Cerium-Doped Zinc Oxide as a Photocatalyst for the Degradation of Antibiotics and the Inactivation of Antibiotic-Resistant Bacteria

Abstract: The threat of antibiotic resistance to the wellbeing of societies is well established. Urban wastewater treatment plants (UWTPs) are recognised sources for antibiotic resistance dissemination in the environment. Herein a novel cerium-doped zinc oxide (Ce-ZnO) photocatalyst is compared to ZnO and the benchmark TiO2-P25 in the immobilised form on a metallic support, to evaluate a photocatalytic process as a possible tertiary treatment in UWTPs. The catalysts were compared for the removal of two antibiotics, trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…DH5α is commonly used laboratory E. coli strain to maintain and amplify small plasmid DNA [43]. More importantly, it is often used in fundamental research of a wide range of new potential antibacterials [44][45][46][47] and even for the production of silver nanoparticles upon transformation [48]. Additionally, it seemed reasonable to model growth curves of this strain since we have thoroughly investigated its growth parameters [40].…”
Section: Minimal Inhibitory and Bactericidal Concentrationsmentioning
confidence: 99%
“…DH5α is commonly used laboratory E. coli strain to maintain and amplify small plasmid DNA [43]. More importantly, it is often used in fundamental research of a wide range of new potential antibacterials [44][45][46][47] and even for the production of silver nanoparticles upon transformation [48]. Additionally, it seemed reasonable to model growth curves of this strain since we have thoroughly investigated its growth parameters [40].…”
Section: Minimal Inhibitory and Bactericidal Concentrationsmentioning
confidence: 99%
“…In particular, chlorination was applied through the addition of sodium hypochlorite and HPC using a previously optimized and trialed cerium-doped ZnO. 28 , 29 Disinfection is carried out to reach the target of <10 CFU/100 mL of E. coli . Four irrigation regime groups composed of six lettuce plants ( Lactuca sativa cultivar: Romaine), each set up and irrigated with one of four water types, namely, chlorinated tWW, HPC tWW, secondary WW (positive control), and fresh water (negative control).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while efficiency in the generation of reactive oxygen species is of high importance in evaluating the efficacy of the photocatalysts, it is not the sole substantial contributor [30,31]. Zammit et al [13] observed a very different behavior in the degradation of two antibiotics by TiO 2 and ZnO photocatalysis, reporting different degradation rates for the two photocatalysts with respect to trimethoprim and sulfamethoxazole.…”
Section: Kinetic Studies In Distilled Watermentioning
confidence: 99%
“…At very low antibiotics concentrations, bacteria are not killed and can develop genes to protect themselves against antibiotics. These genes can then propagate across bacterial strains [11][12][13]. Without further action, ten million people may die each year worldwide due to infectious diseases caused by multi-resistant bacteria by 2050 [14].…”
Section: Introductionmentioning
confidence: 99%